Leadership styles and quiet quitting in school context: unveiling mobbing as a mediator - Ergen, Hüseyin; Giliç, Fahrettin; Yücedağlar, Asena; İnandi, Yusuf (Frontiers in Psychology, 2025)
IntroductionLeadership and mobbing can be the prominent antecedents of quiet quitting behaviours of teachers, which is also linked with their well-being. This relational study examines whether mobbing has a mediating role between teachers’ perceived leadership style and quiet quitting.MethodsThis study employed structural equation modelling to analyse the questionnaire data from 411 teachers working in public schools in Turkey. Confirmatory factor analysis was conducted to determine whether the factor structures of the scales used in the study constituted a valid model, and SEM-based mediation tests were conducted to determine the relationships between the variables.ResultsAutocratic leadership has a positive association with mobbing and quiet quitting while democratic leadership has a negative correlation with them. The structural equation modelling revealed that the level of mobbing perceived by teachers has a partial mediating role between the leadership style of school administrators and teachers’ quiet quitting behaviours.DiscussionThese findings have theoretical and practical implications for leadership studies, organizational behaviour and educational management. It contributes to educational leadership theories by demonstrating that autocratic and democratic leadership styles influence teacher engagement not only directly but also through workplace mobbing.